Integrasi Metode Cerita Pendek dalam Pendidikan Kesiapsiagaan Bencana di MTs Waru Sukoharjo - Pratama, Adinda Dwi Septyasarie; Werdani, Kusuma Estu (Jurnal SOLMA, 2025)
: Disaster mitigation education is essential for school children as a form of early prevention and preparedness enhancement, yet not all schools, including MTs Waru Sukoharjo, provide this training. The objective is to increase the knowledge and preparedness of students at MTs Waru Sukoharjo regarding disasters through educational sessions using the short story book "Adventures Together: Maintaining Security and Safety at School" as an educational medium. Method: The method involves administering questionnaires before and after the intervention to measure changes in knowledge and attitudes. Results: Results from pre-test and post-test show a significant increase in knowledge scores by 19.1% and attitudes by 6.94%, with statistical analysis using t-tests indicating significant improvements. Conclusion: In conclusion, the storytelling method using short story books is effective in enhancing students' understanding and preparedness for disasters, providing a strong foundation for further implementation in the school curriculum.